Anticancer Effect of Hypophyllanthin, Niranthin and Lintetralin From Phyllanthus amarus on HeLa Cells And NIH/3T3 Cells - Noor, Nur Affira Mohd; Nafiah, Mohd Azlan; Tuan Johari, Syed Ahmad Tajudin; Hasnan, Muhammad Hafiz Husna; Tan, Siow Ping; Liew, Sook Yee; Supratman, Unang (MDPI, 2019)
Phyllanthus amarus which is locally known as Dukung Anak was one of the herb used in traditional medicine and research of P. amarus in Malaysia was not widely reported. This present research has isolated three chemical compounds and its anticancer effect of this species has been determined. Three lignans namely hypophyllanthin was afforded from hexane crude while niranthin and lintetralin were afforded from ethanol crude. Anticancer test against HeLa cells and NIH/3T3 cells by MTT assays was tested for its anticancer effect. The result shows that hypophyllanthin was considered to possess an active anticancer effect on HeLa cells than NIH/3T3 cells compared to niranthin and lintetralin. © BEIESP.